O MBA brasileiro na gestão de recursos humanos - Schaffer, Augusto Frederico Caetano (2002)
The study deals with post-graduation courses in Brazil, as criterion for selection developing and updating executives and the main features expected from professionals that concluded these courses. The results of the research, with opinions of Human Resources professionals from the major Brazilian companies, also indicated that the majority of them use these courses and where they were taken as selection criterion for employing executives. In the same way, the study concluded that most of these companies frequently uses post-graduation courses for updating and training their professionals and the courses are frequently chosen by them.